Scaffolding in Mathematics Learning: A Literature Analysis of Its Impact on Conceptual Understanding - Baharuddin (International Journal of Education, Vocational and Social Science, 2026)
Conceptual understanding is a central objective of mathematics education; however, national and international reports consistently indicate that students’ levels of conceptual understanding remain relatively low. One pedagogical approach widely recommended to address this issue is scaffolding, defined as the provision of gradual and temporary instructional support aligned with students’ learning needs. This study aims to systematically examine empirical evidence on the implementation of scaffolding in mathematics learning and its impact on students’ conceptual understanding through a systematic literature review. The study employed a systematic literature review (SLR) methodology. Relevant articles were retrieved from reputable academic databases, covering publications from 2020 to 2025. Seven selected studies were analyzed based on educational context, types of scaffolding, research design, and key findings related to mathematical conceptual understanding. Data were analyzed using thematic synthesis to identify recurring patterns, emerging trends, and existing research gaps. The findings indicate that scaffolding consistently exerts a positive effect on students’ conceptual understanding of mathematics across different educational levels. Conceptual and metacognitive scaffolding were identified as the most effective forms, particularly in fostering relational understanding and deep mathematical reasoning. Furthermore, recent developments in technology-based and digital scaffolding demonstrate considerable potential for enhancing personalized learning, although their effectiveness largely depends on instructional design quality and appropriate fading strategies. This study concludes that while scaffolding is an effective instructional approach, it is inherently complex, underscoring the need for further longitudinal and integrative research to optimize its application in mathematics education.